Considerations for Translating Medical Devices Under Development From the Clinic to the Home: A Case Study in Providing Chronic Wound Care. Issue 1 (June 2021) - Bass, Ellen J.; Sefcik, Justine S.; McLaurin, Elease; DiMaria-Ghalili, Rose Ann
A prototype medical device and protocol that work well in a clinic would not necessarily work reliably in the home setting. The goal of this work is to identify factors to consider when translating a device evaluated in a clinic for use by home caregivers providing chronic wound care for persons living with dementia. One must consider the current device, the associated bundle, the protocol and how they may need to be modified. Semi-structured interviews with the research assistants who have applied a prototype device were conducted to generate a list of known issues with the current clinical protocol in terms of ultrasound application The researchers performed a set of specified tasks by following the current device protocol and explaining any difficulties with use. They embellished the descriptions with details about what had happened with actual patients in the clinic. Using thematic analysis, analysts identified themes and subthemes. Issues potentially relevant to translating medical devices to the home are discussed.